Work of teachers co-organising the process of education of pupils with special educational needs in the opinions of public school teachers - Niemiec, Marta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
One of the key issues within the area of issues related to contemporary special education is inclusive education. The purpose of the presented article is to analyse the key entities participating in the teaching and upbringing of pupils in the public educational system – the roles, tasks, professional qualifications, predispositions and personality traits of teachers of pupils with special educational needs. The article also presents results of research carried out by the author among teachers at public schools in the Silesian Voivodeship.